Influence of Food Plots on Nothern Bobwhite Movements, Habitat Use, and Home Range - L. Andrew Madison; Robert J. Robel; David P. Jones (National Quail Symposium Proceedings, 2017)
Natural resource managers at the Fort Riley Military Reservation in Kansas have established plantings to provide winter food for northern bobwhites (Colinus virginianus) since 1959. These food plots have the potential for reducing movements and home range sizes of bobwhites during winter because birds should apparently need to forage over less area to obtain sufficient food. To determine if this was occurring, we conducted a 3-year radio telemetry study of bobwhites on Fort Riley. We equipped 511 bobwhites with radio transmitters and followed their movements and habitat use from October through March, beginning in 1994. Daily movements of bobwhites near food plots varied by field season and study site, but generally did not differ significantly between food plot and non-food plot areas. Home ranges of bobwhites did not differ significantly between food plot and non-food plot areas, study site, or field season. Prairie habitat always was used significantly less than its proportional availability by bobwhites. Food plots were used significantly more than their proportional availability during 2 of 3 field seasons. Habitat use by bobwhites on the 2 study sites differed between food plot and non-food plot areas.